Uncertainty shocks, adjustment costs and firm beliefs: Evidence from a representative survey - Andreas Dibiasi; Heiner Mikosch; Samad Sarferaz (ETH Zurich, KOF Swiss Economic Institute, 2021)
This paper studies the dynamic effects of an uncertainty shock on firm expectations. We conduct a survey that confronts managers from a representative firm sample with a model-consistent uncertainty shock scenario. An exogenous increase in uncertainty significantly reduces managers' expected investment, employment and production in the short and mid run. We collect novel direct firm-level measures for different types of capital and labor adjustment costs. Adjustment costs vary strongly across sectors and types. They help explain firms' reactions to the shock, which provides evidence for the relevance of real-options channels. We compare the findings to DSGE and VAR results.
hdl:20.500.11850/512724
Keywords: C83; D83; D84; E22; E23; E24; 330; Uncertainty; Shock; Firms; Survey; Vignette; Expectations; Investment; Employment; Production